Photo-synergistic promoted in situ generation of Bi0–BiSbO4 nanostructures as an efficient catalyst for nitrobenzene reduction. Issue 125 (1st December 2015) - Liu, Mengqing; Lv, Li; Du, Xiaomeng; Lang, Junyu; Su, Yiguo; Zhao, Yanxia; Wang, Xiaojing
Abstract : This work reports on the construction of Bi 0 –BiSbO4 nanostructures to show photo-synergistic and efficient catalytic activity toward nitrobenzenes reduction. Abstract : This work reports on the synthesis of BiSbO4 micro-flowers by a facile hydrothermal method. All as-prepared samples were carefully characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. TEM and XPS results indicated that partial Bi 3+ ions in BiSbO4 nanoparticles were in situ converted into metallic bismuth to form Bi 0 –BiSbO4 nanostructures in the presence of NaBH4 during the reduction of 4-nitrophenol. The as-prepared Bi 0 –BiSbO4 was found to be an efficient, renewable and green noble metal free catalyst toward catalytic reduction of nitrobenzenes. Moreover, UV light can promote the reduction of Bi 3+ to metallic bismuth, which can robustly and photo-synergistically accelerate the apparent reaction rate for catalytic reduction of nitrobenzenes into aminobenzenes. The in situ generation of Bi 0 –BiSbO4 nanostructures may provide new possibilities for the development of novel bismuth-based systems for catalytic applications.